2017
DOI: 10.1038/s41598-017-01712-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Specific Disruption of Intracellular Protein Complexes by Hydrocarbon Stapled Peptides Using Lipid Based Delivery

Abstract: Linear peptides can mimic and disrupt protein-protein interactions involved in critical cell signaling pathways. Such peptides however are usually protease sensitive and unable to engage with intracellular targets due to lack of membrane permeability. Peptide stapling has been proposed to circumvent these limitations but recent data has suggested that this method does not universally solve the problem of cell entry and can lead to molecules with off target cell lytic properties. To address these issues a libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…3A and B). Multiple studies have indicated that active transport has a significant role in cellular uptake of stapled peptides, where FAM labeled stapled peptides have been shown to be actively endocytosed into cytoplasmic vesicles (22,23). This is in line with ongoing work in the p53lab on PM2 and other stapled peptides, and with results reported by Yurlova and colleagues (24) demonstrating that inhibition of the MDM2:p53 interaction takes approximately 30 to 60 minutes to occur, as opposed to Figure 4.…”
Section: Discussionsupporting
confidence: 68%
“…3A and B). Multiple studies have indicated that active transport has a significant role in cellular uptake of stapled peptides, where FAM labeled stapled peptides have been shown to be actively endocytosed into cytoplasmic vesicles (22,23). This is in line with ongoing work in the p53lab on PM2 and other stapled peptides, and with results reported by Yurlova and colleagues (24) demonstrating that inhibition of the MDM2:p53 interaction takes approximately 30 to 60 minutes to occur, as opposed to Figure 4.…”
Section: Discussionsupporting
confidence: 68%
“…The enriched localization of EGFP-MOP3 in the nucleus via binding to its targets MDM2 and MDMX suggested that treatment with competitive inhibitors could free EGFP-MOP3 to re-equilibrate throughout the cells. We induced expression of EGFP-MOP3 in the stable cell lines and examined the localization of EGFP-MOP3 after treatment with sMTIDE-02, Nutlin or negative control stapled peptide sMTIDE-02 SCRAM ( Thean et al , 2017 ) by timelapse confocal microscopy (Fig. 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adopted from the viral and gene delivery fields, positive charge is one method of conferring membrane permeability of peptides [6,39,40]. However, methods such as the recombinase enhanced bimolecular luciferase complementation platform (ReBiL) and LDH release quantification highlighted some of the toxicity hurdles inherent in cationic agents and motivated other strategies to achieve membrane permeability [12,38]. Just a few years since the first hydrocarbon stapled peptides were introduced, researchers in the field are developing new membrane permeable peptides with more robust methods of demonstrating on-target efficacy using in vitro assays and giving special attention to physicochemical properties outside of charge that can help improve cytosolic delivery [41][42][43][44].…”
Section: Access To the Cytosolmentioning
confidence: 99%
“…However, there are far fewer reports of in vivo efficacy studies, the precursor to clinical trials, and some of the strategies and mechanisms employed towards efficacy in cells may have deleterious effects in the context of an animal model or patient. Furthermore, various studies have revealed uncertainties in how effectively some of these recently developed peptides penetrate cells and bind their targets [11,12]. Efficient cell membrane permeability is just one of many variables to consider for successful in vivo drug delivery.…”
mentioning
confidence: 99%